Tingkat Literasi Keuangan Syariah Siswa Sekolah Menengah Kejuruan (SMK) di Banjarmasin: Studi Kasus SMK Negeri 1 Banjarmasin - Aneta Rakhmawati; Lea Emilia Farida (BIMA: Jurnal Bisnis dan Manajemen, 2025)
This study aims to describe the level of Islamic financial literacy among vocational high school students as part of an effort to enhance young people’s awareness and understanding of Islamic financial principles. The research employed a descriptive quantitative approach, collecting data through a Likert-scale (1–5) questionnaire covering several indicators of knowledge, attitude, and behavior related to Islamic finance. The analysis showed that students’ Islamic financial literacy level was in the moderate to good category, with average indicator scores ranging from 3.0 to 4.0.. These results suggest that students generally have a positive understanding of Islamic financial concepts and practices, although further practical education and experiential learning are needed to strengthen literacy in real-life contexts. The findings are expected to serve as a basis for developing curriculum content and educational strategies on Islamic finance at the secondary education level.